Learning to Govern Together in Representative Democracy - Thomas König, Xiao Lu, Thiago N Silva (Oxford University Press, 2026)
Learning to Govern Together in Representative Democracy introduces a dynamic theory of coalition governance, focusing on the temporal constraints that coalition parties face when governing together in representative democracies. The book examines how coalition partners, over the course of a legislative term, adapt their strategies for joint policy-making as they encounter varying levels of cooperation and competition in partnership. Two distinct models of learning are developed: the portfolio-learning model, where ministers learn through interactions within their portfolios, and the partisan-learning model, which accounts for learning from co-partisan experiences across portfolios. Empirical evidence from 11 parliamentary democracies demonstrates that ministerial office-holders infer the type of partnership from their experienced parliamentary scrutiny, with consequences for their legislative behavior, such as initiating government bill proposals earlier in the term if they perceive a cooperative partnership, or later in the term if they perceive a competitive partnership. The book makes a significant contribution to our understanding of coalition effectiveness, stability, and satisfaction with governance.